Crop Residue Management in Conservation Agriculture Systems in Zimbabwe Smallholder Farming Sector: Importance, Management Challenges and Possible Solutions - Mhlanga , Blessing; Muoni, Tarirai (Asian Journal of Agriculture and Rural Development, 2014)
Conservation agriculture (CA) is promoted as a cropping system that has potential to alleviate poor crop yields in smallholder farming while protecting the environment. It involves maintenance of permanent soil cover, diverse crop rotations and/or interactions; and minimum soil disturbance. CA is associated with crop residue management challenges due to low crop biomass yields and crop-livestock interactions in Zimbabwean smallholder farming sector. There is competition on crop residue uses causing challenges in retaining adequate crop residues for full benefits of using residues to be realised. Among the crop residues management options fencing fields reduces the chances of crop residues grazing by free roaming cattle during the dry season. Construction of rakes to pile up crop residues where cattle cannot access has been practiced in some communal areas. Farmers have practised the system of taking the crop residue harvest to homesteads into protected areas to reduce risk of grazing. Farmers may use fences around fields to reduce access into fields. However, all these management options require an investment from the farmers who are resource constrained. Farmers may use non-crop residues such as thatch grass and reduce competition for crop residue use where farmers feed them to livestock during the dry season.